1976
DOI: 10.3133/ofr76193
|View full text |Cite
|
Sign up to set email alerts
|

Crossbedding of the Potomac Formation in Fairfax County, Virginia

Abstract: Crossbedding in sandstone units is the most conspicuous sedimentary structure of the Potomac Formation in Fairfax County, Virginia. Most sets of crossbeds are a few feet thick and several feet wide and tens of feet long. Trough sets are dominant, but planar sets are also common. Dip directions of crossbeds show great variation, though westerly dips are sparse. The averages (resultant vectors) of crossbedding dip-directions measured at 33 localities do not show significant differences according to their geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Crossbeds and channel cut-and-fill structures are part of sand-filled channels which range in size from a few meters to hundreds of meters across and extend for kilometers. The sedimentary structures, locally abundant plant accumulations, rare dinosaur remains, and the complete absence of marine fossils also suggest a fluviatile, continental environment of deposition (Weir, 1976).…”
Section: Observations Stratigraphymentioning
confidence: 99%
“…Crossbeds and channel cut-and-fill structures are part of sand-filled channels which range in size from a few meters to hundreds of meters across and extend for kilometers. The sedimentary structures, locally abundant plant accumulations, rare dinosaur remains, and the complete absence of marine fossils also suggest a fluviatile, continental environment of deposition (Weir, 1976).…”
Section: Observations Stratigraphymentioning
confidence: 99%
“…Neither the wells nor outcrops are sufficiently numerous to delineate the subsurface extent of major sand bodies with precision. However, studies of crossbedding in outcrops of the sand bodies have aided this delineation(Weir, 1976). The dip direction of the crossbeds is an indication of the current direction and also 3U~<?d direction of elongation of the sand bodies Weir (1976).…”
mentioning
confidence: 99%
“…However, studies of crossbedding in outcrops of the sand bodies have aided this delineation(Weir, 1976). The dip direction of the crossbeds is an indication of the current direction and also 3U~<?d direction of elongation of the sand bodies Weir (1976). measured dip direction of cross bedding in the « Potomac sands and concluded that the predominate current direction is eastward (average dip direction of 292 crossbeds is N 85°E).…”
mentioning
confidence: 99%
“…The diagram shows that the Potomac Group sediments that overlie saprolite consist of gravelly sands (Kps) and silty or sandy clay (Kpc) that interfinger in a complex manner. These sediments were deposited in a fluviatile environment, and as a consequence, the sands often fill old channels while the clays and silts are associated overbank floodplain deposits, natural levees and ox-bow deposits(Weir, 1976).Under some conditions thick porous sands may serve as aquifers for groundwater, whereas the impermeable clays act as confining beds. An outstanding characteristic of clays that is of concern to planners is the susceptibility of the clay to slump and creep, even on very low angle slopes.…”
mentioning
confidence: 99%